Dampak Pengembangan Pariwisata dan Sikap Nelayan di Desa Pangandaran - Elbie Yudha Pratama; Rilus A Kinseng (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2013)
Development of coastal tourism can give directly impact on the social and cultural life of fisherman communities and influence the attitudes of fishermen. This study intend to analyze the impact of tourism development on the social structure and cultural values as well as analyzing the attitudes of fishermen towards the tourism development. The research was conducted in Pangandaran village using survey methods. The results showed that the development of tourism impact on the social structure of fishermen namely the growth of social organization, social stratification, migration and composition of the population, as well as the livelihoods and incomes. Whereas the impact on the cultural value of fishermen include namely the waning tradition of local fishermen, fishermen lifestyle changes, and increased knowledge of fishermen. Fishermen status and income level have a real relationship with the attitude of fishermen, whereas age and education level did not have a real relationship with the attitude of fishermen.Keywords: tourism development, impact towards social structure, impact towards cultural values, and fisherman attitudes